Urgency of trade reform over trade liberalisation - Hugh Corbet (Intereconomics, 1977)
The GATT system has in recent years revealed a number of dangerous weaknesses. Therefore there is reason for concern not only with the further liberalisation of trade within the accepted framework of GATT rules but with a reform of the rules as well.
Keywords: 330; International Trade